2021
DOI: 10.3390/biology10030229
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Developmental Biology of Acroclisoides sinicus, a Hyperparasitoid of Scelionid Parasitoids

Abstract: Acroclisoides sinicus (Hymenoptera: Pteromalidae) was described in 1988 from China, but recent findings in Europe and North America within the framework of Halyomorpha halys (Hemiptera: Pentatomidae) biological control indicate a Holarctic distribution. The few records and fragmented information on A. sinicus are derived from generic observations of other species belonging to the same genus, and its biological and ethological traits are still completely unexplored. It was suspected to be a facultative or oblig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…[ 28 ]. Recent findings confirmed what was previously supposed, that A. sinicus acts as an obligate hyperparasitoid of pupae of Scelionidae but not of Eupelmidae [ 29 ].…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…[ 28 ]. Recent findings confirmed what was previously supposed, that A. sinicus acts as an obligate hyperparasitoid of pupae of Scelionidae but not of Eupelmidae [ 29 ].…”
Section: Introductionsupporting
confidence: 85%
“…The results obtained in the second no-choice test confirm that A. sinicus is a hyperparasitoid of the pupal stage of Trissolcus sp. The differences among oviposition days can be explained by the host’s different developmental stages or ages [ 29 ]. No sign of hyperparasitism was observed in H. halys eggs that were parasitized by the primary parasitoid 2 days previously, since the Trissolcus pupae were probably not formed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Hymenoptera: Pteromalidae) and Ooencyrtus sp. (Hymenoptera: Encyrtidae) were found in several studies [ 1 , 16 , 25 , 30 ], but these are most likely hyperparasitoid species, as found in other studies [ 16 , 31 , 32 , 33 ], although not all Ooencyrtus sp. are hyperparasitoids [ 34 ].…”
Section: Resultsmentioning
confidence: 79%